2017
DOI: 10.1051/epjn/2017020
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen segregation in pre-hydrided Zircaloy-4 cladding during a simulated LOCA transient

Abstract: Abstract. Oxygen and hydrogen distributions are key elements influencing the residual ductility of zirconiumbased nuclear fuel cladding during the quench phase following a Loss Of Coolant Accident (LOCA). During the high temperature oxidation, a complex partitioning of the alloying elements is observed. A finite-difference code for solving the oxygen diffusion equations has been developed by Institut de Radioprotection et de Sûreté Nucléaire to predict the oxygen profile within the samples. The comparison betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Similarly, Torres [TOR17] and Guilbert [GUI16] contributed to show that this solubility limit is not significantly influenced by hydrogen content up to 1000 wppm.…”
Section: Figure 5: Zr-o Phase Diagram ([Dom76] Solid Lines -Cross Mar...mentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Torres [TOR17] and Guilbert [GUI16] contributed to show that this solubility limit is not significantly influenced by hydrogen content up to 1000 wppm.…”
Section: Figure 5: Zr-o Phase Diagram ([Dom76] Solid Lines -Cross Mar...mentioning
confidence: 88%
“…) . Torres [TOR17] has shown that average hydrogen contents up to 400 wppm had limited influence on this solubility limit, and Guilbert [GUI16] extended this conclusion for temperatures ranging between 1000 and 1200°C. At higher hydrogen contents, an influence of hydrogen content is expected as shown by Guilbert [GUI16].…”
Section: Figure 5: Zr-o Phase Diagram ([Dom76] Solid Lines -Cross Mar...mentioning
confidence: 93%